Hubungan Gambaran Bercak-Bercak Gelap (Dark Specks) pada Latar Belakang Material Nekrotik Granular Eosinofilik dengan Kadar CD4 Penderita Limfadenitis Tuberkulosis Servikalis yang Disertai HIV/AIDS - . Sutoyo Eliandy, M. Nadjib D. Lubis, Delyuzar (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2015)
ABSTRAK Latar belakang Diagnosa limfadenitis TB mudah ditegakkan apabila gambaran-gambaran khas ditemukan pada sediaan aspirasi. Tetapi apabila gambaran ini tidak dijumpai, sulit membedakan antara limfadenitis akut supuratif atau limfadenitis TB supuratif, terutama pada pasien dengan HIV/AIDS. Penelitian ini dilakukan untuk mengetahui hubungan bercak-bercak gelap (dark specks)pada latar belakang material nekrotik granular eosinofilik dengan kadar CD4 penderita limfadenitis tuberkulosis servikalis yang disertai HIV/AIDS. Metoda Penelitian ini menggunakan Exact Fisher Test dengan pemilihan sampel secara consecutive sampling. Hasil Dari 24 sampel penderita limfadenitis TB yang disertai HIV/AIDS dijumpai 20 orang laki-laki (83,3%) dan perempuan 4 orang (16,7%). Umur penderita seluruhnya pada usia produktif dengan rentang umur 21-49 tahun. Ditemukan gambaran dark specks pada 4 sediaan biopsi aspirasi pada kadar CD4 0,05. Kesimpulan Tidak ada hubungan munculnya dark specks dengan kadar CD4 penderita limfadenitis TB yang disertai HIV/AIDS. Kata-kata : Dark specks, Limfadenitis TB, CD4, Antibody ab905 ABSTRACT Objective Diagonosis of liphadenitis TB was easy to established when the spesific images was found in the preparat of aspiration. However, if the image was not found in the preparat, it was dificult to distinguish between supuratif acute lymphadenitis and supuratif lymphadenitis TB, primarily for those patients with HIV/AIDS. This research was carried out to determine the relationship of dark speck image at the eosinophil granular necrotic material background with the level of CD4 to the patient lymphadenitis tuberculosis cervicalis with HIV/AIDS Methods This research was conducted using exact fisher test with the consecutive sampling. Result From 24 samples of patient lymphadenitis TB with HIV/AIDS was found 20 patients were male (83,3%) and 4 female patients (16.7). All of the patients were included into the productive age with the range of age from 21-49 years old. It has been found the dark specks image at 4 samples of biopsy aspiration at level of CD4 below than 200. There were the indication, the dark speck image will be appear when the immune system of patients was decrease. However, base on the result of statistical analysis, it was exhibited that there was no significant different (p>0.05) between dark specks image and CD4 level. Conclusions There was no relationship appearance of dark speck with the level of CD4 to the patient lymphadenitis TB with HIV/AIDS KeyWords : Dark specks, Lymphadenitis TB, CD4, Antibody ab905